A study of emotions in the family business succession - Juuma, Anniina (2013)
The aim of this paper is to analyze the family business literature in order to find out how emotions are studied in the context of family business succession. Methodologically, the data was collected by reviewing the chosen literature. The object is to search how the concept of emotions is understood in the succession process and what definitions of emotions there can be found in the literature. Based on the literature from the field of family business there is conducted a concept analysis. Accordingly the research question guiding this study is: How emotions in the succession process are studied and understood in the literature of family business field? To be able to find answer to this question can help to find an answer also to more important question with wider contribution: What makes generational transition periods a relatively smooth process for some family companies, whereas for other firms it is a period of revolutionary change? This paper aims that enhancing the common definition of the emotional process would increase the knowledge of the succession process. Also widen the studies more empirical level would have benefits. The main arguments behind these statements are the findings that the current models explaining the emotional process in the family business succession still are fragmentary and need to be more standardized.